AB1157 Clinical implications of ultrasonography (US) in monitoring disease activity of relapsing polychondritis (RP) and comparative investigation by us between auricle of rp, repeated trauma and healthy subject. (12th June 2018) - Inotani, S.; Taniguchi, Y.; Nishikawa, H.; Amano, E.; Nakayama, S.; Terada, Y.
Abstract : Background: Relapsing polychondritis (RP) is a rare systemic inflammatory disorder and might often be refractory. Therefore, the discovery of more convenient imaging modality than contrast-CT, MRI and FDG-PET/CT would be required on diagnosis and treatment. Objectives: To assess the clinical implications of ultrasonography (US) in monitoring disease activity and diagnosis of relapsing polychondritis (RP). Methods: Firstly, auricular chondritis of patients with RP (n=5) were assessed by US before and after treatments. Second, the relationship between US findings and other serum inflammatory markers were evaluated. Moreover, the comparisons of US findings between the auricle of patients with RP (n=5), repeated trauma (n=5) which is similar to auricle of RP, and healthy subjects (n=5) were also assessed. Results: US finding before treatment showed low-echoic swollen auricular cartilage with increased power Doppler signals (PDS) in all cases of RP. US findings corresponded to biopsy findings. After treatment with prednisolone (PSL) combined with methotrexate, the swollen ear completely resolved. Then, US findings also showed dramatic reductions in swollen cartilage with the decrease in PDS. When serum inflammatory markers completely improved, but US finding remained in 1 of 5 cases, and this case showed flare due to PSL tapering. Finally, RP could be differentiated from the damage of repeated trauma with producing subperichondrial serous effusion. Conclusions: US of auricular cartilage in RP possibly facilitates evaluation of auricular lesions and monitoring of disease activity, especially when we consider the treatment response and the timing of drug tapering. Disclosure of Interest: None declared